(untitled) (American Journal of Islam and Society, 2001)
Finding Fran is a memoir of two women, once best friends, who take very different paths. The author is now a feminist history professor and her high school friend, Fran, is Noura-a Muslim living in Egypt Banner looks back on their lives to find out what led one to feminism and the other to Islam. Unfortunately, while Banner offers many interesting insights into the lives of both women, she never fully answers this fundamental question. The book is divided into four parts. Part I, "My Story (1944-1952)," explores Banner’s family history as well as her life up Wltil high school. She traces the lives of various family members in order to discover how they affected her childhood and her outlook on life. In the second part, "Fran & Me (1952-1956)," Banner tells the story of their high school friendship. It is a friendship of two smart and artistically talented girls, who are often bold and passionate in a time and place that glorified passive, feminine women. Together they navigate the seemingly esoteric system of football players and prom queens without ever really belonging to that system. In college they separate, Banner to UCLA and Fran to Stanford. This is the beginning of their two different paths. Banner takes to academia and feminism, while Fran is drawn to the various spiritual movements of the 1960s. These years are covered in the third section, "Passages (1956- 1982)." Banner includes chapters on their college life and the years immediately following, and then delves into her life as an academic and a feminist. The last section covers Fran/Noura’s life between 1967 and 1990. She studies Zen and other spiritual movements, such as the Gurdjieff system. In late 1960s, she moves to a commune in New Mexico. There she discovers westernized Sufi practices that have been cut from their Islamic base. Her continuing quest leads her to study Islam. She eventually becomes a Muslim and a member of a traditional Sufi order. Later, she studies in Saudi Arabia, and currently, she residues in Egypt. In keeping with the personal nature of the book, Banner includes a collection of photographs ranging from old family snapshots to the two women together in high school in 1956 and again in Egypt in 1992. Much of Banner’s analysis comes in the prologue and the epilogue. She also includes detailed notes for each chapter ...